If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -9x = 7x + 18 Reorder the terms: 7 + -9x = 18 + 7x Solving 7 + -9x = 18 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 7 + -9x + -7x = 18 + 7x + -7x Combine like terms: -9x + -7x = -16x 7 + -16x = 18 + 7x + -7x Combine like terms: 7x + -7x = 0 7 + -16x = 18 + 0 7 + -16x = 18 Add '-7' to each side of the equation. 7 + -7 + -16x = 18 + -7 Combine like terms: 7 + -7 = 0 0 + -16x = 18 + -7 -16x = 18 + -7 Combine like terms: 18 + -7 = 11 -16x = 11 Divide each side by '-16'. x = -0.6875 Simplifying x = -0.6875
| (7x^3+4x)(x^2+2)= | | 4(x-3)=23-x | | 9(2+x)=63 | | 4x+13=94 | | 2(3-5+7)+6= | | 5(14-x)=60 | | 8(x+1)=48 | | 3x(3+5)=24 | | -32=4(x+3) | | (2x+4y)+(4x+7y)=180 | | -3x^2+21x=15 | | 5x+5+4x+5+35=180 | | 1=-.5(3k-4) | | 3.50x=84 | | (3+3.50)x=84 | | 5m^2+2=47 | | -2/3q+2q=6/5q+12/5 | | 2[(12+2x)+(15+2x)]=74 | | 8y^2-23y-3= | | (-762.46)=h-32.061 | | 4x-12=72 | | x^2-12x-14=41 | | 21.21+p=(-101.6) | | (3u+7)(8+u)=0 | | cos(3x)=cos(x) | | 17x^2-153=0 | | 11/20+5/20 | | 102.8=g(-66.09) | | b-17.8=(-36) | | x^2-5x=12-4x | | 7/8x-1/4+3/8x=1/16x | | 9/35+6/35 |